EMPOWERING ENGLISH WRITING STUDENTS: REFLECTING ON ASPECTS OF THE PROCESS THAT HELPED ME MOST? - Walker, Deron (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2017)
Process-oriented writing instruction has been advocated for both L1 and L2 writing classrooms since the 1960s. Empowering learner autonomymay best occur through non-direct instruction (Rogers Freiberg, 1994), engaging students in social learning (Vygotsky, 1978) andcreating workshop-like classrooms (Murray, 2004). Any number of techniques can be used, preferably in-sync with each other, to accomplish such an approach. This study will examine the results of some recent action research in the classroom to attempt to ascertain among various process-techniques, designed to accomplish the aforementioned aspects of process-oriented instruction,which techniques (CODA paradigm / rubrics, journals, peer reviews, teacher conferences, etc.) were most useful to developmental students, especially from their own points of view. Student voices were collected through oral presentations, instructor evaluations, and classroom observations in an American classroom where native English speaking and non-native English speaking writers wrestled with freshman level developmental writing side-by-side.